METODE EXTREME PROGRAMMING PADA APLIKASI PENDATAAN WARGA BERBASIS ANDROID MENGUNAKAN APP INVENTOR (STUDI KASUS: BTN GRIYA AMBAN PANTAI KABUPATEN MANOKWARI) - Kristia Yuliawan (Jurnal Sistem Informasi dan Informatika (Simika), 2021)
BTN Griya Amban Pantai consists of 54 families who are in the Amban district, Manokwari Regency. In carrying out data collection and recording of residents 'data, the household administrators are still doing it manually, where the household administrators carry out data collection by recording resident data using a form filled out by residents by visiting residents' homes. After the form is filled in, data recording is carried out using a notebook. The problem in carrying out the manual process of data collection and data recording of residents is that when officers come to the residents' houses, often the head of the family or family members is not at home so that the the householdmanagement cannot carry out data collection and data recording. To solve this problem, an Android-based data collection and data recording application is needed using the App Inventor application. The method used in making community data collection and data recording applications uses the extreme programming method where this method can develop applications that are more efficient, flexible, low risk and quick to solve. With this android application, it can simplify the performance of the management of the BTN Griya Amban the household in carrying out data collection and data recording without the need to visit residents' homes to collect and record data. The method used in testing this application is to use the blackbox method where testing is carried out focusing on the functional specifications of the software that has been made.